Acerca de si pudo o no ser el universo anisotrótipico - Alvarado, Rodrigo (2011)
The theoretical and experimetnal problem concerning the origin and formations of the universe is establish in this paper, specially by developing some theories that try to explain this phenomena, and also to settle the reasons why the universe could have been anisotropic and homogeneous at the very beginning, envolving in time later on in what we see today. Besides some other posibilities are studied in order to avoid the singularyty at the beginning of the universe. Some exact solutions are obtained by autoconsistency with the Einstein equations utilizing for that purpose different types of interactions among the spinor and the scalar fields, with and without matter.